Construction of MXene-Based Heterostructured Hybrid Separators for Lithium–Sulfur Batteries - Xiao Zhang; Guijie Jin; Min Mao; Zirui Wang; Tianyu Xu; Tongtao Wan; Jinsheng Zhao (Molecules)
The advancement of lithium–sulfur (Li-S) batteries has been hindered by the shuttle effect of lithium polysulfides (LiPSs) and sluggish redox kinetics. The engineering of functional hybrid separators is a relatively simple and effective coping strategy. Layered transition-metal carbides, nitrides, and carbonitrides, a class of emerging two-dimensional materials termed MXenes, have gained popularity as catalytic materials for Li-S batteries due to their metallic conductivity, tunable surface chemistry, and terminal groups. Nonetheless, the self-stacking flaws and easy oxidation of MXenes pose disadvantages, and developing MXene-based heterostructures is anticipated to circumvent these issues and yield other remarkable physicochemical characteristics. Herein, recent advances in the construction of MXene-based heterostructured hybrid separators for improving the performance of Li-S batteries are reviewed. The diverse conformational forms of heterostructures and their constitutive relationships with LiPS conversion are discussed, and the general principles of MXene surface chemistry alterations and heterostructure designs for enhancing electrochemical performance are summarized. Lastly, tangible challenges are addressed, and advisable insights for future research are shared. This review aims to highlight the immense superiority of MXene-based heterostructures in Li-S battery separator modification and inspire researchers.